2005
DOI: 10.1191/1358863x05vm639ra
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Raynaud’s disease

Abstract: Raynaud's phenomenon is due to transient cessation of blood flow to the digits of the hands or feet. An attack of Raynaud’s phenomenon is classically manifested as triphasic color changes. The white phase is due to excessive vasoconstriction and cessation of regional blood flow. This phase is followed by a cyanotic phase, as the residual blood in the finger desaturates. The red phase is due to hyperemia as the attack subsides and blood flow is restored. An attack is frequently associated with pain and/or pares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 79 publications
2
112
1
Order By: Relevance
“…Cold acra have been found in FS similar to Raynaud's phenomenon (CREST) or even Raynaud's disease, yet less pronounced [98]. The role of endothelial dysfunction in primary and secondary Raynaud's phenomenon has been demonstrated with evidence from various modalities including autonomic nervous stress tests like the cold pressor test [121][122][123][124][125]. It may be regarded a heterogeneous syndrome involving endothelial dysfunction as a key player but not every form entails a propensity for atherosclerosis.…”
Section: Endothelial Dysregulation In Flammer Syndromementioning
confidence: 99%
“…Cold acra have been found in FS similar to Raynaud's phenomenon (CREST) or even Raynaud's disease, yet less pronounced [98]. The role of endothelial dysfunction in primary and secondary Raynaud's phenomenon has been demonstrated with evidence from various modalities including autonomic nervous stress tests like the cold pressor test [121][122][123][124][125]. It may be regarded a heterogeneous syndrome involving endothelial dysfunction as a key player but not every form entails a propensity for atherosclerosis.…”
Section: Endothelial Dysregulation In Flammer Syndromementioning
confidence: 99%
“…A diagnosis of Raynaud's phenomenon (RP) can be made when color changes occur to the skin of the digits of the hands or feet in response to cold temperatures or emotional stress (Levein, 2010). RP is known to be caused by transient cessation of blood flow to the digits of the hands or feet (Cooke & Marshall, 2005). Prior studies have shown that RP is associated with various diseases such as rheumatoid arthritis, scleroderma, dematomyositis, hypertension, and migraine (Gayraud, 2007).…”
mentioning
confidence: 99%
“…Raynaud's phenomenon usually is triggered by cold temperatures, or by emotions such as stress and anxiety (Cooke and Marshall, 2005). The pathological mechanisms are related to the high level of sympathetic activity (Stallworth et al, 1981;Sakakibara et al, 2002;Cooke and Marshall, 2005) and low level of CGRP expression in the local sensory fibers (Mourad and Priollet, 1997;Bunker et al, 1996). The island skin flap animal has been used to mimic the vasospastic condition (Linderoth et al, 1995 b;Qi et al, 2002).…”
mentioning
confidence: 99%